Study on multiplication of some important medicinal plants in G.G.V. Bilaspur, C.G., India. - Patel, D K (Current Botany, 2012)
A medicinal plant includes specific chemical compounds in their body system that may be varying between plants. Genetic constitution and related environmental condition affect the presence of the Medicinal plants in certain area. Destructions of natural habitat is a leading factor responsible for loss of the species in any ecological area. Over exploitation, Diseases etc. are also supporting the extinction of the species. To maintain the existence in nature plants are producing a remarkable number of seeds once or twice in a year. Among a large group of the plants many of the plants are not capable to produces Seeds but such a condition nature has provided them the capacity to regenerate themselves by vegetative mode. Stem cutting, Bud, Leaf, Root are the vegetative parts of the plants are widely used for vegetative propagation. Amount of Seed production and their dispersal mechanism is specific and unique for variable plant species. Seed germination percentage is also changeable from plant to plant. Under vegetative propagation in the plants stem cutting experiment success depends upon the inition of roots and origination of new buds/leaf. The current study focuses on the multiplication of various Medicinal plants which are regenerating by both the methods Seeds as well as by their vegetative parts. The experiment was carried out in planting the Medicinal plants in poly bags. The findings of the experiment are listed in Table -01and discussed furthermore.